PERLINDUNGAN HUKUM TERHADAP BANK ATAS PERJANJIAN KREDIT KONSUMSI BAGI ORANG ASING - Husnul Khotimah, Rachmadani Eka; Luth, Thohir; Widhiyanti, Hanif Nur (Faculty of Law, University of Muhammadiyah Malang, 2018)
Since 2005 the rule of Bank Indonesia is already issued a policy about consumer credit facilities in order to get a place or a home for foreign people who live in Indonesia, but it is not enough to make all the bank that took place in Indonesia give that facilities. One of the reasons discrepancy of a number banks to give that credit facilities to foreign people is because the risk in case there is a failure or the person is not fulfilling the obligation. Considering the debtor is a foreigner, while the object of the guarantee is a land with a right of use that has a limited period, and until now there is still no regulations from both the Indonesian government and from Bank Indonesia that specifically provide protection against banks on consumer credit facilities for foreigners. In this paper, the writer will discuss the effort of legal protection that can be done by the Bank are preventive effort and repressive effort. Preventive legal protection efforts undertaken by banks is with credit agreements. Repressive legal protection effort, if the foreign debtors can not fulfill the obligation one of them is to stop the consumer credit agreement.